2021
DOI: 10.7759/cureus.15502
|View full text |Cite
|
Sign up to set email alerts
|

In The Line of Treatment: A Systematic Review of Paroxysmal Supraventricular Tachycardia

Abstract: Paroxysmal supraventricular tachycardia (PSVT) is a common tachyarrhythmia, and an electrocardiogram is the best tool for making a diagnosis. If Valsalva maneuvers and carotid sinus massage do not give positive results, then the next choice is either adenosine or calcium channel blockers. At this time, adenosine is the drug of choice of treatment. Verapamil and diltiazem are the most commonly used calcium channel blockers (CCBs). This review aimed to compare the efficacy of both drugs in the treatment of PSVT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 2 , 3 Previous studies had reported aberrations in ion channel activity within cardiomyocytes, alterations in cellular communication, and dysregulated calcium handling can be intricately linked with SVT pathophysiology. 4 , 5 Despite the relief offered by current therapeutic interventions like drug treatments and catheter ablation, 6 , 7 some cases persistently resist treatment or are prone to recurrence. This accentuates an urgent need for innovative diagnostic tools, treatments and prognostic markers at the myocardial cellular level to optimize the management of SVT and enhance patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Previous studies had reported aberrations in ion channel activity within cardiomyocytes, alterations in cellular communication, and dysregulated calcium handling can be intricately linked with SVT pathophysiology. 4 , 5 Despite the relief offered by current therapeutic interventions like drug treatments and catheter ablation, 6 , 7 some cases persistently resist treatment or are prone to recurrence. This accentuates an urgent need for innovative diagnostic tools, treatments and prognostic markers at the myocardial cellular level to optimize the management of SVT and enhance patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic compromise and cerebral hypoperfusion may occur. 1 Treatment options include drug therapy or ablation, the choice of which depends on the severity of SVT. 2 Catheter ablation is first‐line therapy for symptomatic, recurrent SVT (Class I), especially among higher‐risk individuals, such as those with preexcited atrial fibrillation or high‐risk occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Supraventricular tachycardia (SVT) refers to rapid arrhythmias (>100/min), originating in tissue within or above the His bundle. Hemodynamic compromise and cerebral hypoperfusion may occur 1 . Treatment options include drug therapy or ablation, the choice of which depends on the severity of SVT 2 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 A recent systematic review showed that adenosine was not only equally efficacious in treating SVT but was also safer than intravenous calcium channel blockers (CCB). 3 Furthermore, another study found adenosine to be a safe and effective treatment for SVT in pre‐hospital settings. 4 It has a success rate of over 90% for terminating SVT.…”
Section: Introductionmentioning
confidence: 99%
“…The standard guidelines for management of SVT state that adenosine should be the first medication therapy if vagal maneuvers fail to terminate SVT 2 . A recent systematic review showed that adenosine was not only equally efficacious in treating SVT but was also safer than intravenous calcium channel blockers (CCB) 3 . Furthermore, another study found adenosine to be a safe and effective treatment for SVT in pre‐hospital settings 4 .…”
Section: Introductionmentioning
confidence: 99%